Studies in Spike Disease of Sandal - Venkata Rao, M. G. (Indian Forester, 1934)
Different methods of inoculation by which spike disease of sandal can be transmitted are described. The fundamental principle in all methods is the grafting of infected tissue on healthy stocks. (2) Twig-grafts which contain a large quantity of infective material always transmit the disease without exception whenever the grafts fuse with the stock. In all other methods of inoculation, that is, buds, patch hark-grafts, ring bark-grafts, and leaf-insertion, though organic connections are formed, the disease develops only in certain percentage of cases varying from 17 to 63 per cent. Depending on the kind of graft used. (3) It is therefore suspected that unlike other similar virus diseases, a minimum amount of the infective agent may be necessary to transmit the disease. There is also indication that some individuals offer more resistance to infection than others. Severe pruning of plants appears to weaken their power of resistance. (4) To ascertain, if there is any seasonal variation in disease transmission, monthly inoculations with ring bark-grafts were conducted all round the year. The highest percentage of transmissions was found among plants operated in the months of May and June, the period of greatest vegetative activity, and lowest among those inoculated in October. (5) The disease is generally not transmitted through haustoria in the case of young saplings 2 to 3 feet high, as their haustoria can attack only the small tender roots of other sandal, which in the case of spiked plants are all dead.